5k-12=-22

Simple and best practice solution for 5k-12=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5k-12=-22 equation:


Simplifying
5k + -12 = -22

Reorder the terms:
-12 + 5k = -22

Solving
-12 + 5k = -22

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 5k = -22 + 12

Combine like terms: -12 + 12 = 0
0 + 5k = -22 + 12
5k = -22 + 12

Combine like terms: -22 + 12 = -10
5k = -10

Divide each side by '5'.
k = -2

Simplifying
k = -2

See similar equations:

| -4x-16=-33 | | cbrt(x)+cbrt(x-16)=cbrt(x-8) | | 1378384.64=4534.16*h | | (x-2)2+(y-4)2=36 | | g(p+3)=2x^2+5x+2 | | 9x-5=32 | | 7(x-3)=(4x+5) | | (2k-1)x^2-7x+(k+9)=0 | | 8a-28+3a=9a | | 22(x-5)+1x=-11-(x-1) | | 2a-19=7a+31 | | 6a-5a=13 | | 12p-16=-44+16p | | (p*p*p)-(1p*2p)=(p*p)+40p | | 4x^2=1764(-25x^2) | | 4x^2=1764-25x^2 | | 4x^2=-25x^2 | | 50+60+x+70=180 | | (p*p*p)-(2p*2p)=(p*p)+40p | | 4z+2+4z=10z-22 | | 5(u-8)-5=-3(-8u+9)-3u | | (6z-46)+33=5z+14 | | 3d+4(d-2)= | | x^2=7+2 | | 2x-10x-12=0 | | 4*3.14(x^2+25x+25)= | | 6t+42=7t+27 | | 5x^2+2x=175 | | 65=5+5x | | 3=2w+7 | | -14uv+4v-21u=0 | | -14uv+4v=o |

Equations solver categories